Tidal current power in Capalulu strait, North Maluku: A feasibility study - Kurniawan, Alamsyah; Azmiwinata, Maulvi; Pratama, Munawir Bintang; Kusuma, Cahya (Center of Biomass & Renewable Energy (CBIORE), 2024)
The Indonesian government has set goals for increasing the use of renewable energy in the coming years. Currently, Indonesia relies heavily on non-renewable energy sources, which poses a threat to the environment due to the country's growing energy needs. This study aims to assess the potential for developing a tidal power plant in Capalulu Strait, North Maluku. Using hydrodynamic modelling, the study identified two potential locations at coordinates 1.877°S – 125.328°E (Capa-2) and 1.863°S – 125.323°E (Capa-4) which were selected for having median current speeds exceeding 1.8 m/s and maximum current speeds exceeding 3.5 m/s. The study tested a hypothetical implementation of KHPS Gen5 instrument(s) by Verdant Power, a 5 m diameter turbine with a rated nominal power of 37 kW and a maximum rated power of 56 kW. A power plant layout was designed to be placed at Capa-2 and Capa-4, each location accommodating 45 turbines. The development of this power plant is estimated to produce up to 22 GWh per year. Financial analysis resulted in a LCOE of IDR 5,930/kWh. However, this price is still high compared to the national electricity tariff of IDR 1,027.70/kWh. Variations in the number of turbines also may not result in a lower LCOE than the national tariff. Nevertheless, the estimated cost of generating electricity is still competitive compared to diesel, which is around IDR 5,804/kWh.